Nitrogen Use Efficiency, Symbiotic N2 Fixation and Transfer in Red Clover-Grass Mixtures - SERIN, YUNUS; IBRAHIM ERKOVAN, H. (Asian Journal of Chemistry, 2010)
In order to be successful in the mixtures of grass and legume harmonious species should be chosen. This research has been mad eto investigate the nitrogen rate, nitrogen use efficieny, fixation and the transfer of red clover (Trifolium pratense L.), smooth brome (Bromus inermis Leyss), orchardgrass (Dactylis glomerata L.), red fescue (Festuca rubra L.) and their binary mixture. According to a two yearaverage results, the efficiency of pure sown grasses is higher than red clover and mixtures. Nitrogen fixation in the alone sowing of red clover is higher, on the other hand, in mixtures, the fixation amount has been higher in which the legume rate is high. The nitrogen transfer from legume to grass has been occurred most in the mixture of red clover and orchardgrass. As the establishment has aged, the nitrogen transfer to grasses has increased while nitrogen fixation has lessened.